Prevalence of chronic hepatitis B virus infection in Thailand: a systematic review and meta-analysis. (October 2016) - Leroi, Charline; Adam, Pierrick; Khamduang, Woottichai; Kawilapat, Suttipong; Ngo-Giang-Huong, Nicole; Ongwandee, Sumet; Jiamsiri, Suchada; Jourdain, Gonzague
Highlights: This is a meta-analysis of chronic hepatitis B prevalence studies in Thailand. Chronic hepatitis B prevalence has decreased dramatically among people born after 1992. There was a significant decrease even before the Thai immunization program was implemented in 1992. Of the three million chronically infected people in 2015, 60% were older than 45 years. The large number of individuals infected is a challenge for future treatment programs. Summary: Objective: To estimate the number of people living in Thailand with chronic hepatitis B (CHB), a major cause of liver cirrhosis and cancer, in view of the implementation of programs to prevent CHB complications. Methods: Using PubMed/Medline and ScienceDirect, all studies reporting hepatitis B surface antigen (HBsAg) seroprevalence estimates conducted in Thailand and published between 1975 and 2015 were reviewed systematically. Pooled prevalence estimates and their 95% confidence intervals (CIs) were calculated, and potential sources of heterogeneity investigated. Results: A high heterogeneity was observed between prevalence estimates. There was a significant decrease in the 150 estimates of HBsAg prevalence with more recent decades of birth ( p < 0.001), even before the implementation of the national universal immunization program in 1992. When restricted to the general population, the pooled prevalence estimate was 5.1% (95% CI 4.3–6.0%), which would translate to an estimated number of individuals with CHB living in Thailand in 2015 as high as three million. Conclusions: The high burden of CHB in Asian countries is a major challenge for the incorporation of national programs to prevent CHB complications within health care systems.